Analisis Hambatan Guru Dalam Penggunaan Media Pembelajaran Berbasis Audio Visual Pada Mata Pelajaran Ekonomi Di SMAN 7 Empat lawang - Yusti Anggun Tiara; Bahrin Bahrin; Duharman Duharman; Ade Irma Suryani (Universitas Dehasen Bengkulu, 2024)
This research aims to determine teachers' barriers to using audio-visual based learning media in economics subjects at SMAN 7 Empat Lawang. This type of research is descriptive qualitative with the object being teacher barriers in using audio-visual based learning media in economics subjects at SMAN 7 Empat Lawang and the research subjects are 3 teachers in economics subjects. Data collection techniques use observation, interviews and documentation. The results of the research show that there are several obstacles for teachers in using audio-visual based learning media in economics subjects at SMAN 7 Empat Lawang, namely lack of time in making power points, feeling comfortable with other methods, lack of teacher skills and creativity, teachers not being fluent in using IT. , it is difficult to find videos that match the material, and there are problems with the internet network.